ANALISIS PERBANDINGAN ASURANSI SYARIAH DAN ASURANSI KONVENSIONAL - Slamet Heri Winarno (Universitas Bina Sarana Informatika, 2015)
Financial business today is dominated by conventional based business that one of them still rely on the system of interest. Along with the changing times and changing one's outlook on life in running the business, the application of conventional financial sisitem be especially burdensome and costly. Until recently emerged alternative financial system that is based on sharia to be able to overcome the problems in the financial business. Islamic system refers to the Quran and Hadith are directly related to the law created by Allah SWT. The basic principle of this system is to avoid gharar, maisir, riba. One of Islamic finance is the sharia insurance. Insurance is one of the non- bank financial institution that serves to collect public funds in order to provide protection risks and uncertainties which caused the catastrophe, accident, or other losses. Insurance is based on the operational system is divided into two types, namely Sharia Insurance and Conventional Insurance. Islamic insurance belonging to the innovation of non- bank financial institutions are new, and based on the principles of Islam, the Sharia is still not known by the public, especially the people of Indonesia that most of the population are Muslim. Based on this phenomenon, hence the need for an explanation of the comparison between the two types of insurance, which would provide its own knowledge for people to choose . Keyword: Islamic insurance, conventional insurance, business